Giant high-order nonlinear and nonreciprocal electrical transports induced by valley flipping in Bernal bilayer graphene - Yuelin Shao; Xi Dai (Physical Review Research)
We investigate the electrical transport properties of the minivalley polarized state proposed recently in slightly doped Bernal bilayer graphene (BLG) in large electric displacement fields. By minimizing the Hartree-Fock (HF) energy functional, we first confirm the appearance of minivalley polarized phase. At the low carrier doping regime, the one-pocket state will be stabilized where only one of the trigonal-wrapping-induced Fermi pockets near the atomic-valley center is filled. Then we study the electrical transport of the one-pocket state by solving the Boltzmann equation. We find that the valley polarization could be easily flopped by an in-plane electrical field, which will lead to hysteresis loop in the direct current (DC) I-V curves. Such irreversible current responses in the DC limit will directly induce strong nonlinear and nonreciprocal alternating current (AC) responses, which has been already observed in the recent experiments on BLG.